Identification and Characterization of Ralstonia solanacearum Species Complex from Ginger (Zingiber officinale) in Semarang Regency, Indonesia - Setiawan, Andree Wijaya; Jayanti, Ruth Meike; Herawati, Maria Marina; Natalia, Kezia; Kusuma, Jonathan Galih Raka (Agro Bali : Agricultural Journal, 2024)
The Ralstonia solanacearum species complex is a highly destructive plant pathogen with a remarkably broad range of hosts, and ongoing discoveries continue to expand its host list. In May 2023, a new type of bacterial wilt affecting ginger (Z. officinale) crops in Semarang Regency, Central Java was reported. Early symptoms included sudden withering of leaves in adult plants followed by complete wilting and darkening of the vasculature, ultimately leading to plant death. This research specifically investigates the spread of Ralstonia solanacearum Species Complex within ginger cultivation in Semarang Regency. Twenty bacterial isolates were collected from soil and diseased Z. officinale plants at twenty different locations. Physiological and biochemical analyses confirmed that the causative agent for Z. officinale bacterial wilt was Ralstonia solanacearum belonging to biovar 3 and 4. The study also revealed that the distribution of this pathogen remains focused in the Banyubiru and Sumowono sub-districts. These findings will enhance our understanding of how Ralstonia solanacearum Species Complex spreads among ginger crops and its impact on them.